Introduction to communication technologies for networked smart cities Chap. 1 - Sharma Sh. K. Shree Krishna; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Chatzinotas S. Symeon; Anpalagan A. Alagan (2021, 2021)
Title screen